2018
DOI: 10.1088/1361-6528/aaac66
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin alumina and silicon nitride MEMS fabricated membranes for the electron multiplication

Abstract: In this paper we demonstrate the fabrication of large arrays of ultrathin freestanding membranes (tynodes) for application in a timed photon counter (TiPC), a novel photomultiplier for single electron detection. Low pressure chemical vapour deposited silicon nitride (Si N ) and atomic layer deposited alumina (AlO) with thicknesses down to only 5 nm are employed for the membrane fabrication. Detailed characterization of structural, mechanical and chemical properties of the utilized films is carried out for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Our group approached the problem from a micro-fabrication/engineering point of view by implementing MEMS technology. Silicon nitride tynodes were fabricated by low-pressure chemical vapor deposition (LPCVD) and aluminum oxide tynodes by means of atomic layer deposition (ALD) [20,21]. Monte-Carlo simulation has shown that the optimum thickness for aluminum oxide tynodes is about 10 nm [3].…”
Section: Novel Vacuum Electron Multipliersmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group approached the problem from a micro-fabrication/engineering point of view by implementing MEMS technology. Silicon nitride tynodes were fabricated by low-pressure chemical vapor deposition (LPCVD) and aluminum oxide tynodes by means of atomic layer deposition (ALD) [20,21]. Monte-Carlo simulation has shown that the optimum thickness for aluminum oxide tynodes is about 10 nm [3].…”
Section: Novel Vacuum Electron Multipliersmentioning
confidence: 99%
“…Monte-Carlo simulation has shown that the optimum thickness for aluminum oxide tynodes is about 10 nm [3]. Therefore, the ultra-thin membranes, with a diameter of 10 to 30 µm, were suspended within a supporting mesh with an array of 64-by-64 small windows [21]. A TEY of 1.57 (2.85 keV) was measured for TiN/SiN films and a TEY of 2.6 (1.45 keV) for TiN/Al 2 O 3 films.…”
Section: Novel Vacuum Electron Multipliersmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also increasingly employed in microelectromechanical systems (MEMS) as functional structures in the form of beams, bridges, and membranes [1][2][3][4][5][6]. The mechanical properties of the thin films are very important to the design and reliability of the devices.…”
Section: Introductionmentioning
confidence: 99%